Pengaruh ibadah sholat dan puasa terhadap kesehatan mental remaja milenial di Pondok Pesantren Al-Washilah Kembangan, Jakarta Barat - Shopiyah, Siti; Aulia, Khilfa Natasya (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
The mental health of millennial adolescents, especially those living in urban areas, shows an increasingly worrying trend of disorders and has become an important issue in the fields of education and religion. Social pressure, academic demands, and exposure to digital media are factors that exacerbate their psychological condition. This community service activity aims to increase students' understanding and awareness of the importance of maintaining mental health, especially in the environment of the Al-Washilah Islamic Boarding School, Kembangan, West Jakarta. In this activity, prayer and fasting are positioned as spiritual means that can strengthen mental resilience and provide peace of mind, based on the values of the teachings of the Qur'an. The research was conducted using qualitative methods with a participatory approach, which included socialization activities, interactive discussions, and literature reviews on Islamic and psychological references. The results show that active involvement in daily worship practices such as the five daily prayers and fasting both obligatory and sunnah contribute significantly to the emotional stability, self-control, and inner peace of the students. These findings emphasize the importance of internalizing spiritual values in adolescent mental health development. This program is also recommended as an alternative model for character building and mental health in other Islamic educational institutions.